2016
DOI: 10.1021/acs.estlett.6b00150
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production in Oxic Lake Waters Potentially Increases Aquatic Methane Flux to Air

Abstract: Active methane production in oxygenated lake waters challenges the long-standing paradigm that microbial methane production occurs only under anoxic conditions and forces us to rethink the ecology and environmental dynamics of this powerful greenhouse gas. Methane production in the upper oxic water layers places the methane source closer to the air–water interface, where convective mixing and microbubble detrainment can lead to a methane efflux higher than that previously assumed. Microorganisms may produce me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
134
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 77 publications
6
134
1
Order By: Relevance
“…Such a decrease cannot be related to exchange with the atmosphere since the atmospheric d 13 C-CH 4 is close to À47‰ (Quay et al, 1999). A possible explanation would be CH 4 production in oxic conditions related to primary production by pathways that remain elusive (Tang et al, 2016) as recently reported in several lakes (Grossart et al, 2011;Bogard et al, 2014;Tang et al, 2014). Such an explanation is consistent with the eutrophic nature of the Dendre Lake and should be further investigated in future.…”
Section: Discussionmentioning
confidence: 57%
“…Such a decrease cannot be related to exchange with the atmosphere since the atmospheric d 13 C-CH 4 is close to À47‰ (Quay et al, 1999). A possible explanation would be CH 4 production in oxic conditions related to primary production by pathways that remain elusive (Tang et al, 2016) as recently reported in several lakes (Grossart et al, 2011;Bogard et al, 2014;Tang et al, 2014). Such an explanation is consistent with the eutrophic nature of the Dendre Lake and should be further investigated in future.…”
Section: Discussionmentioning
confidence: 57%
“…Wetlands contribute to the creation of large reservoirs of biodiversity, improve the quality of surface water, reduce flood risk associated with extreme rainfall, and supply streams during low water periods (Brinson et al, 1981;Fustec and Lefeuvre, 5 2000; Mitsch and Gosselink, 2015;Reddy and DeLaune, 2008;Turner, 1991;Whiting and Chanton, 2001). They are also the site of production and emission of greenhouse gases (GHG), which depend on many factors, including pH, oxidationreduction conditions, and biogeochemical functioning (Bastviken et al, 2004(Bastviken et al, , 2011Wang et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…reshwater lakes may be responsible for as much as 20% of total annual methane emissions from natural sources (1)(2)(3), and supersaturation of methane in oxic water columns has been observed in many lakes (4)(5)(6)(7)(8). Some surface water methane is produced by methanogenesis in anoxic bottom waters, followed by upward diffusive transport or ebullition (9).…”
mentioning
confidence: 99%
“…Aerobic demethylation of organic compounds such as methylphosphonate (MPn) could also contribute to surface water methane release; however, this pathway has been observed only in marine systems (12)(13)(14)(15)(16). Because lakes may release as much methane to the atmosphere as the entire global ocean (8) and since the pathways for surface water methane production are poorly understood (17), a comprehensive characterization of the biological pathways responsible for methane production in these environments is critical to more-accurate predictions of global freshwater methane emissions (8,9,(18)(19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation